2015
DOI: 10.1177/1470595815622491
|View full text |Cite
|
Sign up to set email alerts
|

Work engagement and intercultural adjustment

Abstract: While engagement seems to have promising prospects for predicting organizational behavior in domestic organizations, few scholars have included this in cross-cultural management research. We use survey results from 640 self-initiated expatriate academics in Greater China to study the relation between work engagement and intercultural adjustment. We focus on expatriates in Greater China because in terms of economy, this is a fast growing area and because, with regard to language and culture, this region deviate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 98 publications
1
38
0
1
Order By: Relevance
“…After analysing the data from the questionnaires, interviews, and the review of literature, five distinct content areas were identified as important to be included in a CCOT program. These findings confirm the view of Selmer and Lauring (2016) who stated that an effective CCOT should include topics on local language skills, environmental briefing (information about the geography, climate, housing, schools) information about cultural orientation regarding cultural institutions, value system of host country assimilation of culture (brief episodes describing intercultural encounters, cultural and communication sensitivity. These five distinct content areas could be used in shaping the focus, content, and approach in developing a CCOT program.…”
Section: The Five Component Modelsupporting
confidence: 84%
“…After analysing the data from the questionnaires, interviews, and the review of literature, five distinct content areas were identified as important to be included in a CCOT program. These findings confirm the view of Selmer and Lauring (2016) who stated that an effective CCOT should include topics on local language skills, environmental briefing (information about the geography, climate, housing, schools) information about cultural orientation regarding cultural institutions, value system of host country assimilation of culture (brief episodes describing intercultural encounters, cultural and communication sensitivity. These five distinct content areas could be used in shaping the focus, content, and approach in developing a CCOT program.…”
Section: The Five Component Modelsupporting
confidence: 84%
“…Especially, at the present time, the researchers mainly focused on how to develop adjustments among SIEs by different career competencies (e.g., Cao et al, 2013 ), and they have given less attention on how SIEs are psychologically present during particular moments of adjustment. Most SIEs research focuses on unidirectional adjustment from SIEs to HCNs ( Nolan and Morley, 2014 ; Selmer and Lauring, 2015 ), but this study goes beyond this tradition by considering the process of adjustment from the perspective of both parties (i.e., SIEs to HCNs at the same as from HCNs to SIEs). Traditional expatriate research, which is SIEs-centric, often neglected the roles of HCN colleagues (e.g., Selmer and Lauring, 2014a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, adjustment may influence the work engagement of expatriates, as perseverance will make them ready to achieve top notch work outcomes despite the hardship of managing a remote setting. Expatriates who are adjusted have more attachment to their work assignments and concern about the execution of tasks 26,27. Zhang, Harzing, Fan26 stated that highly adjusted employees obtained higher evaluations of their work assignments compared to their workmates on extra-role and in-role performance, showing that more adjusted employees are better engaged in their work and are ready to go the extra mile.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Expatriates’ degree of success in the adjustment process has an effect on their task performance26,27 and their intention to complete their assignment. In parallel to these findings, we expect a positive relationship between expatriate adjustment and the OCB.…”
Section: Theory and Hypothesesmentioning
confidence: 99%